2007
DOI: 10.1002/macp.200700270
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced, Perpendicular Liquid‐Crystal Alignment on Rubbed Films of a Coumarin‐Containing Polystyrene

Abstract: We synthesized a series of polystyrene derivatives containing coumarin side groups using polymer analogous reactions. The liquid‐crystal (LC) alignment director for these polymer films was found to be perpendicular to the rubbing direction. The contrast ratio and anchoring‐energy values of these polystyrene derivatives were found to be much greater than those of polystyrene and poly(chloromethylstyrene), indicating that the coumarin side groups increase the aligning ability. For example, the anchoring energy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In addition, the presence of bulky aromatic rings on the HEPs backbone structure would give rise to the higher thermal stability of HEPs. 19 Xu et al 20 and Kang et al 21 also reported that the bulky aromatic group could significantly improve the thermal stability of the polymer. In comparison to the weight loss of the polyester composite filled with HEPs, the weight loss of the neat polyester due to thermal decomposition is higher.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…In addition, the presence of bulky aromatic rings on the HEPs backbone structure would give rise to the higher thermal stability of HEPs. 19 Xu et al 20 and Kang et al 21 also reported that the bulky aromatic group could significantly improve the thermal stability of the polymer. In comparison to the weight loss of the polyester composite filled with HEPs, the weight loss of the neat polyester due to thermal decomposition is higher.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…14,21,24,25,31,32,[48][49][50][51][52][53][54][55][56][57][58][59][60][61] Second is photodimerization caused by cinnamate, coumarin, and chalcone. [15][16][17]27,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] Third is polyimide undergoing photodecomposition. [82][83][84] Moreover, polyimide-based photoalignment layers can be designed with a photoreactive group as a side chain or a backbone structure, and polyimide itself can induce…”
Section: Introductionmentioning
confidence: 99%
“…Because photoalignment technique is a highly producible process due to clean process, adaptiveness to large glass, and unrestrictedness to surface morphology. A number of photoreactive polymers, which are photoisomeric [18][19][20], photodimeric [21][22][23][24][25][26], and photodegradable [27][28][29] polymers, have been studied for LC alignment in past decades. Especially, photoreactive polymer containing coumarin group has been considered as a candidate in advanced LC alignment layer due to good thermal property and uniform LC aligning ability [24][25][26].…”
Section: Introductionmentioning
confidence: 99%